PENGARUH PEMBERIAN SEDUHAN HERBA SELEDRI (Apium graveolens L.) TERHADAP PENURUNAN KADAR ASAM URAT DALAM DARAH PADA PASIEN LANSIA - Nency Wahyuni, Nency Wahyuni; Aceng, Aceng Ali Awaludin (LP4M STIKes Karsa Husada Garut, 2023)
Uric acid is the end product of purine metabolism, uric acid produced by the body is called endogenous uric acid while that which comes from food is called exogenous uric acid. Uric acid is produced by the body around 80-85%, while the rest comes from food consumed. Stewed celery contains apiin and apigenin which can be used as a treatment for gout. It is considered safer because it produces fewer side effects and does not require too much money. This study aims to examine the effect of steeping celery herb on reducing uric acid levels in the elderly. Research at the Cisandaan Clinic This research used an experimental design with a pretest-posttest with a control group. Sampling technique with simple random sampling technique. The number of samples is 34 elderly, 17 elderly in the intervention group and 17 elderly in the control group. Respondents in the intervention group were checked for uric acid levels before and after being given the infusion. Before giving the steeping of celery herb, the average uric acid level of the respondents was 7.3 mg/dl, after being given the average uric acid level of the respondents was 6.0 mg/dl. Statistical analysis using the Paired T-Test with test results on 17 elderly in the intervention group showed a decrease in uric acid levels with a p-value of 0.000 (p <0.05). This shows that there is an effect of giving celery herb infusion on reducing uric acid levels in the elderly. In conclusion, based on the results of the study, there was an effect of steeping celery herb on reducing uric acid levels in the elderly. Giving this infusion can be used as a therapy for reducing uric acid levels in the elderly by doing it regularly with 200cc every morning.